Tahapan Pemerolehan Bahasa Anak Melalui Video Youtube Mitigasi Bencana: Studi Kasus pada Nick - Bertholomeus Jawa Bhaga; Muhammad Lautama; Maria Theresia Cita Suci (Faculty of Languages and Arts, Universitas Negeri Padang, 2022)
At the beginning of a child's life, of course, always goes through a stage called language acquisition. With language skills, you can interact with other people. The purpose of this study was to identify the stages of language acquisition in children, a case study on Nick. This research is a qualitative research with a descriptive method that seeks to describe the stages of language acquisition in Nick. The procedure is that data is collected, reduced and analyzed about the stages of language acquisition for Nick. This can be found when Nick invites his parents to avoid disaster hazards with various invitations such as in the disaster mitigation video that he has watched before.